Effect of inclination on oscillation characteristics of an oscillating water column wave energy converter. (1st April 2016) - Iino, Mitsumasa; Miyazaki, Takeaki; Segawa, Hiroshi; Iida, Makoto
Abstract: Oscillating water column (OWC) wave energy converters are adopted in many marine applications such as buoys. This research investigates how inclination-induced changes in motion affect the oscillation characteristics of an OWC. As the collector of the OWC wave energy converter is inclined, the direction of motion of the water column is also inclined because it is constrained by collector walls. To investigate this idea, we developed a mechanical 1-degree-of-freedom oscillator model of an inclined OWC. The usefulness of the mechanical model was confirmed in a water tank test with OWCs inclined at 90° (vertical), 45°, and 18.4°. We then investigated the effect of inclination on the resonance period and the optimum power take-off damping of the OWC. The resonance period was mainly prolonged by the reduced restoring force as the motion direction changed. The optimum power take-off damping of an inclined OWC equaled the radiation damping, as observed in vertical OWCs. Finally, we varied the air chamber volume and observed much smaller effects than when varying the inclination. We conclude that changing the direction of motion affects the oscillation characteristics of OWCs mostly because of the reduction of gravity restoring force. Highlights: A mechanical model of the inclined oscillating water column (OWC) is proposed. The model was validated in water tank tests with inclined cylindrical OWC model. The numerical results of the model well agreed with the experimental data. Inclination was found to increase the resonant period of OWC. The model also reproduced the optimum damping at the resonant period of the OWC.